Role of colloids in traumatic brain injury: Use or not to be used? - Tumul Chowdhury; Ronald B Cappellani; Bernhard Schaller; Jayesh Daya (Wolters Kluwer Medknow Publications, 2013)
Trauma is a leading cause of death worldwide and traumatic brain injury is one of the commonest injuries associated with it. The need for urgent resuscitation is warranted for prevention of secondary insult to brain. However, the choice of fluid in such cases is still a matter of conflict. The literature does not provide enough data pertaining to role of colloids in head injury patients.In this article, we have tried to explore the present role of colloid resuscitation in patient with head injury.